2018
DOI: 10.5897/ajbm2017.8463
|View full text |Cite
|
Sign up to set email alerts
|

Business strategy and environmental practices: Evidence in the sugarcane energy sector in Brazil

Abstract: One of the main concerns of this study is to translate environmental practices into strategic actions. This paper aims to analyze how a representative segment of the Brazilian agribusiness, the Mato Grosso do Sul sugarcane industry, is dealing with environmental management at the strategic level. Three data sources were used, which are: semi-structured interviews, questionnaire, and a review of documents and reports. The analysis of interview and documents was carried out through content analysis. Data triangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…On the other hand, Mary et al (24) found several implications for companies in the agroindustrial sector, particularly those involved in the production and management of sugarcane energy in Brazil. Da Silva Souza et al (25) present an index to evaluate doi: 10.25100/iyc.v26i1.13436…”
Section: Sugarcane and Ethanol Companies In Brazil Have Sought Manage...mentioning
confidence: 99%
“…On the other hand, Mary et al (24) found several implications for companies in the agroindustrial sector, particularly those involved in the production and management of sugarcane energy in Brazil. Da Silva Souza et al (25) present an index to evaluate doi: 10.25100/iyc.v26i1.13436…”
Section: Sugarcane and Ethanol Companies In Brazil Have Sought Manage...mentioning
confidence: 99%
“…Thus, in this study, the participants were asked to indicate their financial performance trend for the past 3 years on the seven-point Lickert scale. Melo et al (2018) recommended that businesses of all sizes engage in strategic planning practices in order to survive volatile environments. The empirical evidence on the practice of strategy formulation, as well as its impact on performance in SMEs, is inconclusive.…”
Section: Financial Performancementioning
confidence: 99%
“…Strategy formulation is considered a fundamental strategic management aspect that enhances firm performance, especially in the unstable and dynamic business world (Auka & Langat 2016;Melo et al 2018).…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…The need to understand the strategic management processes of small and medium enterprises (SMEs) has been the primary focus for many authors (Conz et al, 2017). The current unpredictable operating environment requires enterprises of all sizes to engage in proper management practices, particularly those relating to strategy formulation (Melo et al, 2018). Strategy formulation, a key facet of strategic management (Pasha & Poister, 2017), is one of the main processes through which enterprises identify and interpret strategic issues and events that may have a potential impact on their growth (Majang & Magang, 2017).…”
Section: Iintroductionmentioning
confidence: 99%
“…Small and Medium Enterprises are currently operating in highly volatile environments, therefore, making it imperative for a business to develop and implement effective strategic formulation strategies (Melo et al, 2018). For these strategies play a vital role in enhancing better performance and the survival of the business (Williams et al, 2020).…”
Section: Iintroductionmentioning
confidence: 99%